RUSSIA-CHINESE COOPERATION IN THE SCOPE OF INNOVATIVE BUSINESS PRO-JECTS, UNDER THE BUSINESS PLATFORM OF CHINESE UNIVERSITIES - F. Sharipov; A. Rodionov; Z. Ge (Вестник университета, 2017)
The Chinese government has invested considerable resources to the development of innovative ability and skills of students with a view to create competitive advantages for their goods on the world and inner market, and increase social welfare by moving to a new level of production of goods and services. These changes are related with higher education and organizational change in the Chinese enterprises what found reflection in this article.